A 5-year analysis of weight cycling practices in male world champion professional boxer: Potential implications for obesity and cardiometabolic disease - Morehen, J. C.; Langan-Evans, C.; Hall, E. C. R.; Close, G. L.; Morton, J. P. (International Journal of Sport Nutrition and Exercise Metabolism, 2021)
Weight cycling is thought to increase the risk of obesity and cardiometabolic disease in nonathletic and athletic populations. However, the magnitude and frequency of weight cycling is not well characterized in elite athletes. To this end, we quantified the weight cycling practices of a male World Champion professional boxer competing at super middleweight (76.2 kg). Over a 5-year period comprising 11 contests, we assessed changes in body mass (n = 8 contests) and body composition (n = 6 contests) during the training camp preceding each contest. Time taken to make weight was 11 ± 4 weeks (range: 4-16). Absolute and relative weight loss for each contest was 12.4 ± 2.1 kg (range: 9.8-17.0) and 13.9% ± 2.0% (range: 11.3-18.2), respectively. Notably, the athlete commenced each training camp with progressive increases in fat mass (i.e., 12.5 and 16.1 kg for Contests 1 and 11) and reductions in fat-free mass (i.e., 69.8 and 67.5 kg for Contests 1 and 11, respectively). Data suggest that weight cycling may lead to "fat overshooting" and further weight gain in later life. Larger scale studies are now required to characterize the weight cycling practices of elite athletes and robustly assess future cardiometabolic disease risk. From an ethical perspective, practitioners should be aware of the potential health consequences associated with weight cycling.